Indeks Ekologi Gastropoda di Kawasan Perairan Kecamatan Tilamuta Kabupaten Boalemo - Faradila Putri Nasaru; Miftahul Khair Kadim; Sitty Ainsyah Habibie; Sandrianto Djunaidi (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2025)
This study aimed to determine gastropod diversity and the current ecological conditions of the waters in Tilamuta District, Boalemo Regency. Sampling was conducted in April 2025, distributed across three stations. Samples were collected during low tide using a belt transect method covering an area of 150 m2. Identification results revealed a total of 2204 gastropod individuals, representing 12 families: Columbellidae, Cerithiidae, Conidae, Cypraeidae, Strombidae, Littorinidae, Turbinidae, Trochidae, Muricidae, Neritidae, Patellidae, and Vasidae, with a total of 21 species identified. The Shannon Diversity Index (H') indicated a low level of diversity (H' < 2) in the study area. Conversely, the dominance index for the study site ranged from 0.75 to 1.00, signifying a high level of dominance. Furthermore, evenness patterns, as indicated by the J' and Ep indices, all showed values below 1, suggesting an uneven distribution of gastropod species. The study results reveal that the aquatic environment of Tilamuta District, Boalemo Regency, shows signs of pollution, stemming from impaired environmental conditions in the waters, evidenced by low biodiversity.